Adapting Mozambique : representations of violence and trauma in Mozambican cinema and literature - Mulliken, Douglas (Centre for Film and Media Studies, 2015)
This dissertation examines the ways in which violence and trauma are represented in two novels - Lídia Jorge’s A Costa dos Murmúrios (1988) and Mia Couto’s Terra Sonâmbula (1992) - and the cinematic adaptations of those novels - Margarida Cardoso’s A Costa dos Murmúrios (2004) and Teresa Prata’s Terra Sonâmbula (2007). All four works take place in Mozambique and actively engage with the two primary conflicts that occurred in that country - the Mozambican War of Independence (also known as the Anti-Colonial War), fought between 1964 and 1974, and the Mozambican Civil War, fought between 1977 and 1992. In order to provide suitable context for the textual and theoretical analysis found in the body of the dissertation, the study begins by providing a brief review of the history of cinema in Mozambique, focussing primarily on the period stretching from the start of the Anti-Colonial War in 1964 to the present day. It also examines the concept of national cinema, and whether such an idea is justifiable in a Mozambican context. The study continues by considering, in Chapter 2, the concept of adaptation and its limits. This chapter also provides an historical background for some of the atrocities committed during the Mozambican Civil War. Chapter 3 consists of close textual analysis of the two versions of A Costa dos Murmúrios. The chapter identifies two main themes running through both works - the question of subjectivity and a postmodern presentation of history, and the tense, erotic relationship that exists between the two main female protagonists of the narrative, both of whom end up the victims of severe trauma. Chapter 4 looks at the literary and cinematic incarnations of Terra Sonâmbula, with special attention paid to the function of magical realism in both works. This chapter argues that Couto uses magical realism as a sort of coping mechanism which allows his characters to remain hopeful, while the relative absence of magical realism in Prata’s film results in an entirely different representation of both the Mozambican Civil War and the experience of those who lived through it. This work concludes by arguing against too essentialist an understanding of how we define and categorise works of art, regardless of medium. Finally, it calls for further English-language scholarship in the field of Lusophone African cinema.